Analisis Pertumbuhan Ekonomi di Indonesia dengan Pendekatan Error Correction Model (ECM) - Amala, Farida; Susilowati, Dwi (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of exports, imports, labor, investment, and information and communication technology (ICT) on the growth of Gross Domestic Product (GDP) in Indonesia using the Error Correction Model (ECM) approach. The data used are time series data from 2006 to 2023 obtained from the World Bank and the Central Statistics Agency (BPS). The results of the study indicate that exports and ICT have a positive and significant influence on GDP growth in both the short and long term. Imports show a positive influence in the long term, but a negative influence in the short term. Meanwhile, labor and investment are not significant on GDP growth in both periods. The conclusion of this study emphasizes the importance of export diversification, strategic import management, improving the quality of the workforce, investment effectiveness, and accelerating digital transformation in supporting Indonesia's economic growth. The implications of this study provide insight for policy makers to strengthen the competitiveness of the national economy through optimization of the trade and technology sectors.